OC-041 SHEEN PAAJANEN GROIN RECOMMENDED TREATMENT 'SPORT' SCORE FOR GROIN PAIN. (13th October 2022) - Sheen, A J; Biswas, S; Stathakis, P; Jamdar, S; Harwood, R; Paajanen, H
Abstract: Introduction: Evaluating groin pain still evades many clinicians with at times difficulty in determining the cause of pain when no true hernia exists. This study's aim was to evaluate a simple and novel reproducible scoring system, to help determine whether conservative measures or surgery should be recommended for the management of groin pain attributable to inguinal disruption. Methods: Patients that underwent surgery or conservative management for inguinal disruption from 2018 to 2020, with at least one year follow-up, were evaluated with the proposed scoring system. The scoring system is based on MRI and ultrasound imaging as well as clinical findings, with scores given from -2 to +2 based upon the defined findings listed. The sensitivity (ability of SPoRT score to correctly identify physiotherapy required) and specificity (ability of SPORT score to correctly identify surgery required) were calculated for each potential cut off point. The Youden Index was used to find the cut off which optimises specificity and sensitivity. Results: A total of 172 patients were evaluated over a two-year period, n=33 (19%) underwent conservative measures with physiotherapy and rehabilitation the mainstay of treatment, whilst n=139 (81%) underwent surgery to repair diagnosed inguinal disruption. All the patients were males. The table below summarises the mean scores. Physiotherapy Group n=33 Surgery Group n=139 Mean Score (SD) -1.33 (1.92) 1.84 (1.16) Median (LQ, UQ) -1.00 (-3.00, 0.00) 2.00 (1.00, 3.00) Min -5.00 -1.00 Max 5.00 5.00 A ROC curve was used to determine the optimal cut off for the SPORT score to correctly identify people who can have physiotherapy. The ROC curve has an area under the curve (AUC) of 0.936 (95% confidence interval: 0.874, 0.997) suggesting that the SPoRT scoring system is very good at distinguishing between cases requiring surgery and cases where physiotherapy can be used in this data set. Sensitivity and specificity were weighted equally to determine the optimal cut off. SPoRT scores of 0 and lower indicate physiotherapy should be used, whilst 1 and higher indicate surgery. The sensitivity at this cut off is 0.909 (95% confidence interval 0.757, 0.981); the specificity is 0.892 (95% confidence interval 0.828, 0.938). This means the cut off can correctly determine if someone needs physio 90.9% (95% CI: 75.7%, 98.1%) of the time and can correctly determine if someone needs surgery 89.2% (95% CI: 82.8, 93.8%) of the time. Conclusion: In this dataset, SPoRT score of 0 or less can recommend a patient should undergo conservative measures or physiotherapy as a mainstay of treatment, a score of 1 or greater can recommend surgery. Further validation of the scoring system is required.